2017
DOI: 10.2298/mpns1708245d
|View full text |Cite
|
Sign up to set email alerts
|

Severe infection of the anterior abdominal wall in a patient with diabetes mellitus: A case report

Abstract: Introduction. Necrotizing soft tissue infection is a severe, life threatening infection, with high mortality rate, especially in patients with comorbidities. Case report. We are presenting a 53-year-old female patient with diabetes mellitus and a severe infection of the anterior abdominal wall resulting from a vulval infection. The treatment consisted of an extensive excision of the abdominal wall necrosis and surgical eradication of the deep infection source, hyperbaric oxygen therapy, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Necrotizing Fasciitis (NF) is severe and potentially fatal, aggressive infection associated with significant morbidity and mortality. Some literature data reported that the prevalence of NF is about 1-4 cases per 100.000 populations; men are commonly affected, with a male-to-female ratio of 3:1 [1]. However, there are studies showing different results, so, male to female ratio by Eke et al is approximately 10:1 [5], and in the study of Kim et al, men accounted for 67.1% [6].…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Necrotizing Fasciitis (NF) is severe and potentially fatal, aggressive infection associated with significant morbidity and mortality. Some literature data reported that the prevalence of NF is about 1-4 cases per 100.000 populations; men are commonly affected, with a male-to-female ratio of 3:1 [1]. However, there are studies showing different results, so, male to female ratio by Eke et al is approximately 10:1 [5], and in the study of Kim et al, men accounted for 67.1% [6].…”
Section: Discussionmentioning
confidence: 93%
“…There is no age predilection for NF, but patient age is a significant predictive factor for treatment outcome. Patients in the middle-ages and older than 50 years of age are more likely to be infected [10], have a worse prognosis, especially if they have more comorbidities [1,11]. In the study by Chalya PL et al, the median age of patients was 34 years [11], while Schröder A at al.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations